Teologi Islam Kontemporer dan Etika Lingkungan: Pendekatan Maqasid Dalam Mewujudkan Keberlanjutan - Mashadi, Ali Imron (Sekolah Tinggi Ilmu Ekonomi Syariah Riyadlul Jannah Mojokerto, 2025)
This study explores the integration of contemporary Islamic theology and the expanded framework of maq??id al-shar??ah to construct a holistic Islamic environmental ethics model, termed eco?maq??id. Drawing upon the metaphysical concepts of taw??d (Divine Oneness) and wahdat al-wuj?d (unity of existence) as articulated in Sufi cosmology, particularly by Seyyed Hossein Nasr, the research situates nature not merely as a physical entity but as a sacred manifestation of the Divine. Concurrently, the dynamic and multi-dimensional character of maq??id al-shar??ah, particularly through the works of contemporary scholars such as Jasser Auda, provides a normative foundation for ecological stewardship rooted in Islamic legal and ethical values. By synthesizing these two epistemological domains, the study proposes eco?maq??id as a transformative model that bridges spiritual consciousness with normative responsibility, responding to the complex challenges of global ecological crises. Employing a qualitative-conceptual methodology through critical analysis of classical and contemporary Islamic literature, the findings demonstrate that eco?maq??id not only offers a spiritually grounded ethical response to environmental degradation but also possesses practical relevance for sustainability education, public policy, and religious ecological advocacy. This model repositions Islamic theology as a key contributor to interdisciplinary sustainability discourses while reaffirming Islam’s moral imperative to protect the environment as an extension of Divine trust (am?nah). The study concludes with the recommendation to operationalize eco?maq??id in environmental governance and to further empirical research on its application in Muslim societies.